PENERAPAN MEDIA PERMAINAN BLOCK DIENES DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS II SDN 5 SIGLI - Junaidah; Sarah Al Maida (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
The purpose of this study was to determine how the application of Block Dienes game media can improve the learning outcomes of 2nd grade students of SDN 5 Sigli. The research method used is Classroom Action Research (CAR) with Kemmis and McTaggart model design with three cycles. Data collection techniques used in this study were observation, tests, documentation, data analysis techniques using qualitative and quantitative. The subjects of this study were 21 of 2nd grade students consisting of 11 male students and 10 female students. The results of the study showed that in cycle I the average score was 66.09 with 6 students completing it with a percentage of 29%. In cycle II the average score was 81.04 with 14 students completing it with a percentage of 67% and in cycle III the average score was 93.19 with 21 students completing it with a percentage of 100%. The results of this study indicate that the application of Block Dienes game media can improve the learning outcomes of 2nd grade students of SDN 5 Sigli.